Marketing aspects of market orientation of Slovak industrial enterprises in purchasing - Kita, Jaroslav; Grossmanová, Marta; Kita, Pavol (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
Orientation on market is becoming a new instrument of modern industrial enterprises with regard to the fact that the speed of response to the behaviour of customers, suppliers and competition requires mastering a great amount of information which is important for the formulation of an enterprise marketing policy. At the same time it concerns the core of problem solving of a marketing manager, who is wishing to change the company culture in the sphere of purchase in favour of one which is more market oriented. The approach of the article is characterized by two levels: a theoretical one, which presents the synthesis of present scientific knowledge on this specific problem, and an operational one, which is presented by the research results, illustrating and explaining the concept of market orientation in the purchase sphere of industrial enterprises
Argumenta Oeconomica, 2008, No 2 (21), s. 109-124
Keywords: market orientation concept; purchase o f industrial enterprises; suppliers; market research; competitiveness; przedsiębiorstwo przemysłowe; relacja dostawca-odbiorca; badanie rynku